2011
DOI: 10.3109/10826084.2011.569965
|View full text |Cite
|
Sign up to set email alerts
|

Changing Drinking Styles in Denmark and Finland. Fragmentation of Male and Female Drinking Among Young Adults

Abstract: A traditional heavy intoxication-oriented drinking style, "heroic drinking," is a central drinking practice in Denmark and Finland, especially among men. However, it seems that another drinking style leading to intoxication, "playful drinking," has become more prevalent in Denmark as well as in Finland. Playful drinking is characterized by self-presentations in diverse forms of game situations in which you need to play with different aspects of social and bodily styles. We approach the positions of heroic drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 21 publications
3
57
0
1
Order By: Relevance
“…Drinking for social reasons was a clear type of alcohol consumption among these young people (Comasco et al, 2010;Demant & Törrönen, 2011;Mathijssen et al, 2012;Reboussin et al, 2006;Steinhausen & Metzke, 2003;Stewart & Power, 2002). Social drinkers noted drinking at parties with other individuals made them feel more outgoing and social (Comasco et al, 2010).…”
Section: Social Drinkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Drinking for social reasons was a clear type of alcohol consumption among these young people (Comasco et al, 2010;Demant & Törrönen, 2011;Mathijssen et al, 2012;Reboussin et al, 2006;Steinhausen & Metzke, 2003;Stewart & Power, 2002). Social drinkers noted drinking at parties with other individuals made them feel more outgoing and social (Comasco et al, 2010).…”
Section: Social Drinkersmentioning
confidence: 99%
“…Alcohol facilitates group interactions, meeting new people and feeling a sense of belonging in a group (Comasco et al, 2010;Demant & Törrönen, 2011;Jackson et al, 2014). Drinking for social reasons was a clear type of alcohol consumption among these young people (Comasco et al, 2010;Demant & Törrönen, 2011;Mathijssen et al, 2012;Reboussin et al, 2006;Steinhausen & Metzke, 2003;Stewart & Power, 2002).…”
Section: Social Drinkersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially visible for social drinking, regardless of the level of consumption. As Demant and Torronen (2011) emphasize, this process, observed in several countries, is related to an increase in women's activity (including alcohol drinking) in public places, a decline in social perceptions of female drinking as immoral, and adoption of a more playful drinking style (as opposed to heroic drinking) by boys. Moreover, in our study, we observed increasing rates of abstinence among boys beginning in the mid-2000s.…”
Section: Cluster Characteristics Across Yearsmentioning
confidence: 99%
“…Moderate social drinkers are sometimes called "competent" drinkers, since they do not enter into risky situations related to drunkenness (Bogren, 2006), while heavy social drinkers tend to have heavy-drinking episodes but do not drink alone (Christiansen, Vik, & Jarchow, 2002). Demant and Torronen (2011) distinguish "heroic" and "playful" styles among heavy, intoxication-oriented drinkers; the first is characterized by extreme, individual experiences, while the second is more audience oriented and controlled.…”
mentioning
confidence: 99%